DEVELOPMENT OF ANDROID-BASED MATHEMATICS LEARNING MEDIA TO IMPROVE CRITICAL THINKING SKILLS OF HIGH SCHOOL STUDENTS IN WEST SULAWESI - Rezki Novianti; Ana Muliana M; Jeranah; Muhammad Nurhusain (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to develop an Android-based mathematics learning media using Smart Apps Creator (SAC) and determine its validity, practicality, and effectiveness in improving critical thinking skills of high school students in West Sulawesi. This research is a research and development (R&D) with a modified Borg and Gall model and is limited to the product revision stage after the trial. The resulting product is an Android-based Mathematics E-Module that contains interactive materials, learning videos, problem-solving-based practice questions, learning games, and evaluations. The data collection technique used expert validation questionnaires, teacher and student response questionnaires, and critical thinking ability tests. Data were analyzed using a Likert scale, validation tests, practicality tests, and effectiveness tests through a comparison of pretest and posttest results and N-Gain calculations. The results showed that the developed learning media was in the very feasible category based on the assessment of material experts and media experts with a feasibility percentage above 85%. The practicality test showed that teacher and student responses were in the practical to very practical category. The effectiveness test showed an increase in students' critical thinking abilities in the moderate to high category, and there was a significant difference between the pretest and posttest scores. Thus, Android-based mathematics learning media using Smart Apps Creator is effective for improving the critical thinking abilities of high school students in West Sulawesi.